Análisis y diseño de los procesos para la implementación de un sistema de gestión de relación con los clientes en la Empresa Nastel de la parroquia Zapotal. - Espinoza Aguirre, Leonardo Javier (2023)
This case study will be carried out in the ISP Nastel located in the Zapotal parish, whose objective is to analyze and design processes to improve the management and relationship with customers. A correct linkage allows not only to maintain customer satisfaction, but also to generate loyalty and increase profitability. A CRM is a technological tool that helps companies to collect, organize and analyze relevant data in order to improve decision making, increase operational efficiency and strengthen customer relationships. Recognizing the strategic importance of establishing a relationship management system to improve their business results and consolidate their position in the market, the design of processes to meet and improve these needs is studied.